Agro- meteorological Indices in Relation to Phenology and Yields of Promising Wheat Cultivars in Chitwan, Nepal - Amgain, Lal P (Journal of Agriculture and Environment, 2013)
Agro-meteorological indices are the major yield governing factors especially under rainfed ecosystem. The major agro-meteorological indices (phenology, and heat and radiation use efficiencies) of four wheat cultivars were evaluated from the rainfed field experiment (2008-09). The experiment was conducted in RCBD with three replications. The total rainfall received during the winter season (1994-95 to 2008-09) showed satisfactory winter rainfall during wheat growing season except year 2008-09. The agro-meteorological results indicated that the number of days required to attain different phenological stages were comparatively longer in early sowing than the late sown wheat. None of the wheat cultivars could show stable yield in late planting conditions suggesting early planting for higher yield. Early sowing wheat achived the higher and stable heat, radiation and heliothermal indices thus resulting into higher grain yield. The agro-meteorological indices could therefore be helpful in predicting the phenology, growth and yields of wheat. However, more research is needed in other agro-ecological areas to validate the output further.